Forjando a revolução: a cultura política priista (1946-1988) - Pagotto, Aline Maria de Carvalho [UNESP] (2015)
This research analyzes the PRI political culture back in 1946 till 1988. The term PRI refers to the Institutional Revolutionary Party (PRI) from Mexico, which won the political and cultural scene of the country during the mentioned time. However, it did not emerge in 1946, as can be concluded. It opened in 1929 as a alternative to the chaotic post-revolution period, obtaining the following name: National Revolutionary Party (PNR 1929-1938). The opening of PNR obeyed the firmament of Maximato (1929-1936) and the election of pnristas until 1938. This year, the President Lazaro Cardenas (1934-1940) started a reform in the party because it was growing apart of the main objectives of the Mexican Revolution (1911-1920). The change turned out to be structural and ideological, leaving it with a more radical outfit. This resulted in even a change of nomenclature, which came to be called the Party of the Mexican Revolution (PRM, 1938-1946). But had only an elected president, Avila Camacho (1940-1946). After all, in 1946, his successor, Miguel Aleman (1946-1952) established a new reform, claiming that the ideals of the revolution had crystallized in the state institutions. The PRM was then renamed and became: Institutional Revolutionary Party. This change represented, above all, a turn of the party to the right wing. Then, it elected presidents till 2000. With so many discussions on this complex Mexican period and PRI‟s presidents, this research comprehends the perspective of an Italian sociologist, Giovanni Sartori, which proclaims the existence of a hegemonic pragmatic party system, played by the PRI and existent between 1929 and 2000. In addition, from 1946, it became necessary to develop a political culture of the party to the party supporters, so it would discipline and guide them through the new structural and ideological changes. Consequently, this political culture emerged and consolidated as an...